Respuesta :

Given expression: [tex]4 x^{2}+2 y[/tex] for x = 3 and y = –2

(6) Mistake did by Grayson:

In second step, first to do 3² and then multiply with 4.

But Grayson first multiply 4 with 3 and then squared the expression.

This is wrong.

(7) Mistake did by Emily:

In third step, first to multiply 2 with (–2)  using BODMAS rule and then add with 36.

But Emily first added 36 with 2 which gives 38.

This is wrong.

(8) Mistake did by Pat:

In first step, the y value given is –2.

But Pat substituted y value is 2.

This is wrong.

(9) Correct evaluation:

[tex]4 x^{2}+2 y=4(3)^{2}+2(-2)[/tex]

              [tex]=36+2(-2)[/tex]

              [tex]=36+(-4)[/tex]

             [tex]=32[/tex]

This is the correct way to evaluate the given expression.

ACCESS MORE